Thermal Evaporation Deposition of Few-layer MoS2 Films - Ma, Xiying; Shi, Miaoyuan (Nano-Micro Letters, 2013)
We present a study of the fabrication of monolayer MoS2 on n-Si (111) substrates by modified thermal evaporation deposition and the optoelectrical properties of the resulting film. The as-grown MoS2 ultrathin film is about 10 nm thick, or about a few atomic layers of MoS2. The film has a large optical absorption range of 300–700 nm and strong luminescence emission at 682 nm. The optical absorption range covered almost the entire ultraviolet to visible light range, which is very useful for making high-efficiency solar cells. Moreover, the MoS2/Si heterojunction exhibited good rectification characteristics and excellent photovoltaic effects. The power conversion efficiency of the heterojunction device is about 1.79% under white light illumination of 10 mW/cm2. The results show that the monolayer MoS2 film will find many applications in high-efficiency optoelectronic devices.